Corporate political strategies and firm performance: indications of firm-specific benefits from personal service in the U.S. government - Hillman, Amy J.; Zardkoohi, Asghar; Bierman, Leonard (Strategic Management Journal, 1999)
Firms employ a variety of political strategies (e.g., lobbying, contributions) in an attempt to gain influence or access to the public policy process. A variety of benefits may accrue to firms that are successful in creating a linkage with the government: information, access, influence, reduced uncertainty and transaction costs, etc. However, the direct benefits of such strategies are difficult to observe. One political strategy is studied here—personal service (having a firm representative serve in a political capacity). Event-study methodology results show that such linkages with the government positively affect firm value. These findings indicate that firm-specific benefits may result from political strategies. Copyright © 1999 John Wiley & Sons, Ltd.